Inter‐vessel pitting and cavitation in woody Rosaceae and other vesselled plants: a basis for a safety versus efficiency trade‐off in xylem transport - WHEELER, JAMES K.; SPERRY, JOHN S.; HACKE, UWE G.; HOANG, NGUYEN (Plant, cell and environment, 2005)
ABSTRACT The hypothesis that greater safety from cavitation by air‐seeding through inter‐vessel pits comes at the cost of less porous pit membranes with greater flow resistance was tested . Sixteen vessel‐bearing species were compared: 11 from the Rosaceae, four from other angiosperm families, and one fern. Unexpectedly, there was no relationship between pit resistance (and hence the prevailing membrane porosity) and cavitation pressure. There was, however, an inverse relationship between pit area per vessel and vulnerability to cavitation (r2 = 0.75). This suggests that cavitation is caused by the rare largest membrane pore per vessel, the average size of which increases with total pit area per vessel. If safety from cavitation constrains pit membrane surface area, it also limits vessel surface area and the minimum vessel resistivity. This trade‐off was consistent with an approximately three‐fold increase in vessel resistivity with cavitation pressure dropping from −0.8 to −6.6 MPa. The trade‐off was compensated for by a reduction in the percentage of vessel wall pitted: from 10–16% in vulnerable species to 2–4% in resistant species. Across species, end‐wall pitting accounted for 53 ± 3% of the total xylem resistivity. This corresponded to vessels achieving on average 94 ± 2% of their maximum possible conductivity if vessel surface area is constrained.